PENDAMPINGAN PENULISAN KHAT ARAB DASAR DALAM MENUNJANG MAHARAH KITABAH SANTRI MADRASAH DINIYAH BANI ZAWAWI KENCONG - Furoidah, Asni; Ulyah, Manzilatul (INAIFAS Press, 2025)
Learning calligraphy for students, especially beginners, is crucial for developing their ability to write Arabic correctly. However, not all educators are able to devote sufficient attention to calligraphy. One way to advance writing skills (maharah kitabah) is through learning calligraphy for beginners. This study aims to improve the maharah kitabah through writing calligraphy so that students become more familiar with Arabic script from various perspectives. In this community service research, the researcher used the Participatory Action Research method. The results of this study indicate that providing students with calligraphy to Madrasah Diniyah Bani Zawawi Kencong Jember can facilitate the development of maharah kitabah in the learning process. In this case, writing calligraphy is very helpful and makes it easier for students to learn to write Arabic correctly.